G169(P) Systematic Review of a series of Child Protection audits. (7th April 2014) - Abbas, E; Kearney, A; Gopal, S; Sukri, N; Kattakayam, C; Krishnamoorthy, S; Chronopoulo, E; Onel, F
Abstract : Introduction: Approximately 85 children per year die because of maltreatment in the UK. Over 600, 000 children are referred to social care. In 2012, 42, 700 children were on the Child Protection Plan (CPP). Aim: 1. To identify the pattern of various forms of child abuse. 2. To assess our compliance with national guidelines to improve our service. Methods: Retrospective review of 8 audits completed over 8 years. Data was collected from 2005 – 2012 from 555 cases referred to our service. Prospective audit proformas, case files, Electronic Patient records, NAI medical reports and peer review minutes were used. Results: On average, 70% of assessments were completed at rapid access clinics. Cases showed bruising (45%), bite marks (4%), burns (5%) and abrasions/cuts (7%). Referrals were made mostly by Social care (74%), GPs (7%) and A&E (5%), and were due to physical abuse (90% v 60%) and neglect (7% v 25%) in 2005 v 2012 respectively, as awareness of various forms of abuse, increased. Consent for assessment improved over time (28% in 2005 v 97% in 2012). In 2005 assessments were carried out in various locations; by 2012 all cases were assessed in the hospital setting. Assessments were made by Consultants in 22% v 39% cases, Paediatric trainees in 5% v 48% and CMOs in 72% v 13% of cases in 2005 v 2012 respectively. The uptake of investigations (19% v 36%) and photographs (22% v 97%) improved between 2005 to 2012 respectively. The outcomes of assessment showed 30% were conclusive NAI whilst 11% were neglect. The number of children on the CPP increased from 186 to 323 over time, and our number of LAC increased to over 500. In 2012, a new flagging system was introduced to alert physicians to children on the CPP. 85% of children known to the CPP are now flagged as such. Conclusions: Significant changes and improvements in our safeguarding system were seen over this 8 year period as a result of these audits. National recommendation compliance also improved as a result of various local and joint policies, peer review supervision forums and various commissioned staff training courses.